Proteomic Response to Rising Temperature in the Marine Cyanobacterium Synechococcus Grown in Different Nitrogen Sources - Li, Yuan-Yuan; Chen, Xiao-Huang; Xue, Cheng; Zhang, Hao; Sun, Geng; Xie, Zhang-Xian; Lin, Lin; Wang, Da-Zhi (Frontiers in Microbiology, 2019)
Synechococcus is one of the most important contributors to global primary productivity, and ocean warming is predicted to increase abundance and distribution of Synechococcus in the ocean. Here, we investigated molecular response of an oceanic Synechococcus strain WH 8102 grown in two nitrogen sources (nitrate and urea) under present (25°C) and predicted future (28°C) temperature conditions using an isobaric tag (IBT)-based quantitative proteomic approach. Rising temperature decreased growth rate, contents of chlorophyll a, protein and sugar in the nitrate-grown cells, but only decreased protein content and significantly increased zeaxanthin content of the urea-grown cells. Expressions of csoS2 protein involved in carboxysome formation and ribosomal subunits in both nitrate- and urea-grown cells were significantly decreased in rising temperature, whereas carbohydrate selective porin and sucrose-phosphate synthase were remarkably up-regulated, and carbohydrate degradation associated proteins, i.e. glycogen phosphorylase kinase, fructokinase and glucose-6-phosphate dehydrogenase, were down-regulated in the urea-grown cells. Rising temperature also increased expressions of three redox-sensitive enzymes (peroxiredoxin, thioredoxin and CP12) in both nitrate- and urea-grown cells. Our results indicated that rising temperature did not enhance cell growth of Synechococcus; on the contrary, it impaired cell functions, and this might influence cell abundance and distribution of Synechococcus in a future ocean.